Quotations in Qualitative Studies: Reflections on Constituents, Custom, and Purpose. (29th October 2020) - Eldh, Ann Catrine; Årestedt, Liselott; Berterö, Carina
Qualitative studies are often found to be accompanied by quotations from interviews or similar data sources. As with any methodological tradition, it is essential to critically explore the general principle of including quotations in scientific papers: what is the purpose and justification for including quotations? Are there standards and, in that case, what are they and what are their scientific positioning? This paper presents an overview of the somewhat diverse guidance found in the literature in reference to the representation of quotations. Yet, both students and scholars use a variety of approaches to quote from their data, ranging from presenting numerous, extensive, and/or comprehensive quotations throughout the results section to the reporting of a few particular quotations to illustrate certain aspects of the findings only. While their function may be described, scientific reasoning for using quotations is scarce. Along with an overview of the scientific background and options for including quotations in qualitative studies, we discuss the consequences of the different epistemological and methodological aspects found in the literature. In conclusion, we argue that there are incentives for promoting a more deliberate employment of references from data; deriving from the human sciences tradition, a corresponding epistemological stance would suggest that quotations preferably apply for illustrating the analysis process and/or findings, while the idea that quotations can be employed to validate findings has limited support. Further critical examination of the application of and justification for including quotations in the reporting of qualitative studies is needed among researchers, journal editors and reviewers.